(untitled) (Fiep Bulletin - online, 2014)
The correct characterization of hypercholesterolemic models involves the knowledge of the effect of diet on parameters the go beyond lipid metabolism and that nevertheless reflect the effect of the hypercholesterolemic diet on the development of the animals. Equally important, the exact notion of the magnitude of the stress provoked by physical training helps the understanding of its effect on the objects of investigation and guide the choice of the better protocol to be utilized in different experiments. In the present study 48 female adult Fisher rats were distributed in 4 groups: Exercise (swimming 30 min/day, 5 days/week) with hypercholesterolemic diet, exercise with control diet, sedentary with hypercholesterolemic diet and sedentary with control diet. After 9 weeks animals were sacrificed. Results show that exercise was efficient in improving the ratio HDL/LDL and there was an effect on total protein values and kidney weight of the animals. There was no alteration in the structure of the femur bone induced by training. The results indicate that low intensity trainning is capable of altering positively the protein profile and suggest that new studies be performed with different volume and intensity of exercise.